2022
DOI: 10.21203/rs.3.rs-1721079/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Photocatalytic degradation of tetracycline hydrochloride by novel Fe3O4/g-C3N4/rGO magnetic nanocomposites mechanism: modeling and optimization

Abstract: The photocatalytic degradation of antibiotics requires a good separation efficiency of photogenerated electron-hole pairs and a wide visible light absorption range. Current studies have discussed the successful preparation of ferroferric oxide/graphite carbon nitride/reduced graphene oxide (Fe3O4/g-C3N4/rGO). The phase structure and morphology of Fe3O4/g-C3N4/rGO composites were characterized by XRD, HR-TEM, SEM and EDS. The obtained composites were used to degrade tetracycline hydrochloride to evaluate its ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Fe 3 O 4 /g-C 3 N 4 /rGO exhibited 86.7% degradation rate of tetracycline hydrochloride, following pseudo-secondorder kinetics. 613 The proposed mechanism suggested •O 2 − and •OH radicals as the most reactive species in the photocatalytic degradation of tetracycline. Ghoreishian et al 614 reported sonophotocatalytic degradation of tetracycline using a flower-like rGO/CdWO 4 composite under simulated visible-light irradiation.…”
Section: Rsc Applied Interfaces Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Fe 3 O 4 /g-C 3 N 4 /rGO exhibited 86.7% degradation rate of tetracycline hydrochloride, following pseudo-secondorder kinetics. 613 The proposed mechanism suggested •O 2 − and •OH radicals as the most reactive species in the photocatalytic degradation of tetracycline. Ghoreishian et al 614 reported sonophotocatalytic degradation of tetracycline using a flower-like rGO/CdWO 4 composite under simulated visible-light irradiation.…”
Section: Rsc Applied Interfaces Reviewmentioning
confidence: 99%
“…Binary and ternary graphitic composite materials have been reported as photocatalysts in the removal of tetracycline from aqueous solution. [605][606][607][608][609][610][611][612][613][614][615][616][617][618][619][620][621] According to Ren et al, 605 a red mud/graphene oxide (mass RSC Applied Interfaces Review ratio: 93 : 7) composite attained the best degradation rate for tetracycline (79.8%) compared to raw red mud under visible light within 80 min owing to its enhanced specific surface area, light absorption and charge separation. Porous hydroxyapatite (Hap) hollow microspheres as a source of cheap and green photocatalysts have been harnessed in fabricating rGO/Hap composites.…”
Section: Rsc Applied Interfaces Reviewmentioning
confidence: 99%